The Digital Reinvention of Philanthropy: Reconfiguring Good Zakat Governance in Traditional Networks - Hikmatus Sa'diyah (Journal of Digital Economic Studies, 2026)
This study analyzes the implementation of the principles of Good Zakat Governance (GZG) in the digital fundraising strategy at LAZ Sidogiri Bangkalan Branch and evaluates its effectiveness on the performance of Zakat, Infak, and Sedekah (ZIS) fund collection. Using a Mixed Method Sequential Explanatory approach, this study combines an in-depth qualitative analysis of governance practices with a quantitative evaluation based on 2023–2024 financial reports. The results reveal that LAZ Sidogiri implements a hybrid fundraising model that synergizes the strength of the pesantren cultural network with financial technology instruments. The GZG principles, particularly transparency and accountability, are inherently integrated through digital reporting mechanisms on social media and double transaction validation. Quantitative analysis shows a positive growth trend in fund collection, mainly driven by a significant increase in the digital retail infaq segment, with the collection effectiveness ratio falling into the highly effective category. These findings confirm that digitalization accelerates public trust and financial stability for institutions. This study recommends expanding digitalization in fund distribution to match the speed of collection and optimize the social impact for mustahik.